BS EN IEC 61558-2-1. Safety of transformers, reactors, power supply units and combinations thereof. Part 2-1. Particular requirements and tests for separating transformers and power supplies incorporating separating transformers for general applications (29th August 2019) - British Standards Institution,
No abstract available